Architecture as the background to collective life - Goldman, Anna Scott (School of Architecture, Planning and Geomatics, 2017)
This project develops an approach towards the arrangement and design of the primary elements - public facilities and spaces - that necessarily complement the provision of subsidised housing in South Africa. The historical response to the housing shortage in South Africa has been the provision of a remarkable number of individual housing units, but with insufficient funds and attention given to the urban infrastructure, public spaces and facilities that go hand in hand with housing in livable urban environments. This project considers a subsidy housing project where the social facilities are considered upfront, and are seen as an opportunity to create interesting, people-centred places in the development - this thesis is the search for an architecture which forms the backdrop, and framework for growth, for collective urban life. This paper is structured around six sections: thinking, siting, urban design, programming, making and designing. These sections explore, respectively, the theoretical proposal with regards to social facilities and public spaces, the strategic siting of an area of subsidised housing and its associated primary elements, an urban design proposal for the whole development, the programming of the whole site and the individual cluster of facilities that I consider in more detail, the spatial and technological realisation of the public fronts of three case study buildings, and finally the exploration and manifestation of these ideas through a design. My project is being done in conjunction with another student, Rob Richardson, who is looking at creative housing within the limit of the government subsidy. Together we make a proposal for an overall living environment which takes the form of an acupunctural insertion of subsidised housing and the associated primary elements into an area of Wynburg, Cape Town.